The Design of Microstrip Antenna Using DGS and Series Parasitic Methods for C-Band Applications in Satellite Communications - Rusdiyanto, Dian; Muslim , Muslim; Astuti , Dian Widi; Adhiyoga , Yohanes Galih; Apriono , Catur (Universitas Medan Area, 2025)
This research proposes the design of a microstrip antenna for satellite communication that operates at C-Band frequency. The antenna is made of FR4 material with a thickness of 1.6 mm and has a permittivity of 4.4. The target C-Band frequency that can operate is in the range of 3.7 GHz - 8 GHz. To achieve this wide bandwidth, the defected ground structure (DGS) method is used which cuts the ground area under the substrate. Furthermore, to increase the antenna gain, the method of adding parasitic elements arranged in series (series parasitic) located at the top of the patch. The antenna design begins by designing the antenna in the DGS model and adding three parasitic elements where the basic shape of the parasitic elements has the same dimensions as the antenna patch. Then the development is created using a quarter of the patch dimensions which are added with nine parasitic elements. The simulation results show that the antenna with nine parasitic elements has an antenna bandwidth of 5.292 GHz in the range of 3.214 GHz - 8.506 GHz, where the maximum gain obtained is 8.6 dBi. While the development of an antenna with nine parasitic quarter-size patches has a bandwidth of 6.126 GHz in the frequency range of 3.344 GHz - 9.47 GHz with a maximum gain of 8.04 dBi. Therefore, it can be concluded that this research that designs antennas with the DGS method and series parasitic can operate at C-Band frequencies and can be applied to satellite communications.